Stomaphis mordvilkoi Hille Ris Lambers (Aphidoidea, Lachnidae) Oriental aphid recorded on walnut in Northern Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
Stomaphis mordvilkoi H.R.L., a Lachnidae aphid previously described from India, is now reported in Northern Italy where it lives on walnut trunks (Juglans regia). Parthenogenetic apterous viviparous female is described and illustrated making comparisons with dose species.